Classification of physical status and anesthetic risk of dogs undergoing osteosynthesis (Research, Society and Development, 2022)
The majority of orthopedic events in small animals reported in routine clinical practice comprise traumatic fractures. In most cases, surgical treatment is indicated. All patients undergoing a surgical procedure need a careful preoperative evaluation to stablish a safe anesthetic protocol. This evaluation reduces the risk of complications The American Society of Anesthesiologists (ASA) classification is an important tool that links to the patient medical record and can potentially decrease anesthetic and surgical risks. The present study aimed to classify 33 canine patients referred for surgical osteosynthesis, according to their physical status and anesthetic risk corresponding to the American Society of Anesthesiologists classification. After clinical and laboratorial evaluation, the patients were classified by a single evaluator. There was no ASA I patient because this category includes only healthy animals. The ASA II category comprised 12 patients (12/33; 36.36%), considered as suffering from mild systemic diseases. Nineteen patients were classified as ASA III (19/33; 57.57%); these presented with complicated fractures. Only one patient with polytrauma was classified as ASA IV. There were no patients in ASA V or VI and there were no deaths. The results show that among dogs referred for surgical osteosynthesis in the analyzed service and period, the majority were classified as ASA III.